Море остывших желаний: [роман] / Лариса Соболева - Соболева Лариса Павловна (Леди Va-bank, 2007)
Экземпляры: аб. (2007) / Инвентарный номер: 51319 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 54 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44